2023
DOI: 10.3390/microorganisms11102389
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Different Encapsulation Techniques on the Viability and Stability of Diverse Phage under Simulated Gastric Conditions

Sicelo B. Dlamini,
Adriano M. Gigante,
Steven P. T. Hooton
et al.

Abstract: Salmonella causes a range of diseases in humans and livestock of considerable public health and economic importance. Widespread antimicrobial use, particularly in intensively produced livestock (e.g., poultry and pigs) may contribute to the rise of multidrug-resistant Salmonella strains. Alternative treatments such as bacteriophages have shown promise when used to reduce the intestinal carriage of Salmonella in livestock. However, the digestive enzymes and low pH encountered in the monogastric GI tract can sig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 72 publications
0
1
0
Order By: Relevance
“…Their study demonstrated effective encapsulation (>95%) and maintenance of viability (>87%) of five genetically diverse bacteriophages representing three genera after exposure to simulated gastric conditions (pH 2, 3.2 mg/ml pepsin, 37°C, for 1 hour). All bacteriophages were easily released from microcapsules at pH 7.5 and exposure to simulated duodenal conditions (pH 7, 10 mg/ml pancreatin, 37°C) ( 119 ). Eudragit S100 has been widely used as an encapsulation material for targeted bacteriophage release in the colon ( 5 ).…”
Section: Optimizing Formulation and Encapsulation Strategies For Phag...mentioning
confidence: 99%
“…Their study demonstrated effective encapsulation (>95%) and maintenance of viability (>87%) of five genetically diverse bacteriophages representing three genera after exposure to simulated gastric conditions (pH 2, 3.2 mg/ml pepsin, 37°C, for 1 hour). All bacteriophages were easily released from microcapsules at pH 7.5 and exposure to simulated duodenal conditions (pH 7, 10 mg/ml pancreatin, 37°C) ( 119 ). Eudragit S100 has been widely used as an encapsulation material for targeted bacteriophage release in the colon ( 5 ).…”
Section: Optimizing Formulation and Encapsulation Strategies For Phag...mentioning
confidence: 99%